Guyana's national biodiversity strategy and action plan (2012-2020), approved by the Cabinet of the Government of Guyana, May 2015 (Environmental Protection Agency GeorgetownGY, 2015)
Presents information on Guyana's obligations to the Convention on Biological Diversity (UNCBD); a brief history of the prepoation of the plan; the vision, strategic objectives and a snapshot of the priority areas and key actions related to biodiversity which will be implemented during the period 2012 to 2020.
Keywords: BIODIVERSITY